The relationship between oil prices and long-term interest rates - Christopher Phillip Reicher; Johannes Friederich Utlaut (Kiel Institute for the World Economy (IfW), 2010)
We estimate a seven-variable-VAR for the U.S. economy on postwar data using long-run restrictions, taking changes in long-run interest rates and inflation expectations into account. We find a strong connection between oil prices and long-run nominal interest rates which has lasted throughout the entire postwar period. We find that a simple off-the-shelf theoretical model of oil prices and monetary policy, where oil prices are flexible and other prices are sticky, in fact predicts a strong relationship if inflation and oil prices were driven by monetary policy. The observed magnitude of this relationship is still a bit of a puzzle, but this finding does call into question the identification techniques commonly used to identify oil shocks.
Keywords: E31; E58; N50; 330; Oil shocks; interest rates; inflation; Mineralölpreisschock; Zins; Inflationsrate; Inflationserwartung; Geldpolitik; Schätzung; USA